Copper complexes with bibracchial lariat ethers: from mono- to binuclear structures - Rodríguez-Infante, Covadonga (2001)
Copper(II) complexes with a series of bibracchial lariat ethers are described. Independently of the nature of the counterion present (nitrate or perchlorate), the lariat ether N,N'-bis(2-aminobenzyl)-1,10-diaza-15-crown-5 (L1) always forms mononuclear complexes, whereas the lariat ethers N,N'-bis(2-aminobenzyl)-4,13-diaza-18-crown-6 (L2) and N,N'-bis(2-salicylaldiminobenzyl)-4,13-diaza-18-crown-6 (L3) only give binuclear compounds. The X-ray crystal structure of [CuL1](ClO4)2 shows a seven-coordinated copper(II) ion in a distorted (axially compressed) pentagonal-bipyramidal geometry. The X-ray crystal structure of [Cu2(L3-2H)](ClO4)2 confirms the binuclear nature of the compound with both metal ions having identical coordination environments and each one placed out of the crown hole but efficiently encapsulated by the corresponding pendant arm; each copper(II) ion is five-coordinated with an intermediate geometry between trigonal-bipyramidal and square-pyramidal ([tau]=0.40). The EPR spectra in frozen solution samples are in accordance with a stable coordinate pattern for the metal centre of ligand L1, yielding a rhombic distorted complex with axial compression in solution, in agreement with the X-ray crystal structure of [CuL1](ClO4)2. For the binuclear complexes of L2 and L3, the Cu(II) centres in solution can be distorted from their tetragonally elongated structures via interaction with ethanol and/or the nitrate counterion, leading to more than one species.